AMARTYA SEN AND EQUAL CAPACITIES IN ORDER TO ENCRYPT THE RIGHT TO ADEQUATE FOOD - Lima Verdan Rangel, Tauã (LINKSCIENCEPLACE, 2026)
The 1988 Constitution establishes clearly that the dignity of the human person (Article 1, item III) forms the basis of the Federative Republic of Brazil and establishes a series of funda mental objectives, in its article 3, sections I to IV, namely: building a free, fair and supportive society; Guarantee national development, eradicate poverty and marginalization, and reduce social and regional inequalities; Promote the good of all, withou t prejudice of origin, race, sex, color, age and any other forms of discrimination. However, the debate on the level of protection of fundamental rights persists, especially because of the reading of an intimate and umbilical relationship nourished by the very foundation of the dignity of the human person. Thus, the article addresses, in the light of Amartya Sen’s perspective, the recognition of the fundamental right to adequate food, one of the most recent rights included in the broad article 6 of the Fede ral Constitution. In this respect, the aim of the present is to recognize the universalization of the right to adequate food, in its dimensions and orbits, as inseparable from human development and the realization of the dignity of the human person. As a c onclusion, Amartya Sen’s perspective on fundamental rights contributes to the promotion and universalization of the law in question, and calls for recognition of a system of protection of such rights, with the objective of ensuring A fair and egalitarian s ociety. An approach of theoretical nature and, as methodological procedure, of bibliographic, documentary and des criptive research was employed.